The dead romantics - Poston, Ashley (Jove, 2022)
"Ghost meets The Bold Type in this sparkling adult debut about a disillusioned millennial ghostwriter who, quite literally, has some ghosts of her own, from nationally bestselling author Ashley Poston. Florence Day is a ghostwriter for one of the most prolific romance authors in the industry, and she has a problem-after a terrible break-up, she no longer believes in love. It's as good as dead. When her new editor, a too-handsome mountain of a man, won't give her an extension on her book deadline, Florence prepares to kiss her career goodbye. But then she gets a phone call she never wanted to receive, and she must return home for the first time in a decade to help her family bury her beloved father. For ten years, she's run from the town that never understood her, and even though she misses the sound of a warm Southern night and her eccentric, loving family and their funeral parlor, she can't bring herself to stay. Even with her father gone, it feels like nothing in this town has changed. And she hates it. Until she finds a ghost standing at the funeral parlor's front door, too tall and too broad to be her father, and he's just as confused about why he's there as she is. Romance is most certainly dead . . . but so is her new editor, and his unfinished business will have her second-guessing everything she's ever known about love stories"--